Synthesis of Furoxans (1, 2, 5‐oxadiazole 2‐oxides) from Styrenes and Nitrosonium Tetrafluoroborate in Non‐Acidic Media and Mechanistic Study. (25th June 2015) - Matsubara, Ryosuke; Ando, Akihiro; Saeki, Yuta; Eda, Kazuo; Asada, Naoki; Tsutsumi, Tomoaki; Shin, Yong Soon; Hayashi, Masahiko
Abstract : Diverse furoxans (1, 2, 5‐oxadiazole 2‐oxides) were synthesized from the corresponding styrenes using nitrosonium tetrafluoroborate as thenitrosation reagent in pyridine (basic media) or dichloromethane (neutral media). Acid‐sensitive functional groups were tolerated under these conditions. The probable reaction mechanism was elucidated. The experimental results support an ionic reaction pathway in contrast to the conventional acidic conditions with a radical mechanism. Abstract :